2020
DOI: 10.21203/rs.3.rs-59432/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms Associated with Methotrexate-induced Nausea in Juvenile Idiopathic Arthritis

Abstract: BackgroundContext: Methotrexate (MTX) is a cornerstone in the treatment of juvenile idiopathic arthritis (JIA). MTX treatment is commonly associated with nausea. Large inter-individual variation exists in the level of MTX-induced nausea, possibly due to genetic factors. Purpose: To investigate whether MTX-induced nausea was associated with single nucleotide polymorphisms (SNPs) in genes encoding MTX-transporter proteins, a MTX metabolizing enzyme and a nausea receptor.FindingsMethods: Children aged ≥9 years tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Kyvsgaard et al recently found that the rs4149056 SNP in the SLCO1B1*5 and *15 alleles was not associated with MTX-induced nausea in a sample of 121 pediatric patients with JIA, but did find an association with the rs1801133 SNP in MTHFR that we did not investigate in this study. 23 Our sample size of 202 patients is one of the largest for a retrospective cohort study of MTX intolerance. However, there are some limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kyvsgaard et al recently found that the rs4149056 SNP in the SLCO1B1*5 and *15 alleles was not associated with MTX-induced nausea in a sample of 121 pediatric patients with JIA, but did find an association with the rs1801133 SNP in MTHFR that we did not investigate in this study. 23 Our sample size of 202 patients is one of the largest for a retrospective cohort study of MTX intolerance. However, there are some limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Kyvsgaard et al recently found that the rs4149056 SNP in the SLCO1B1 *5 and *15 alleles was not associated with MTX‐induced nausea in a sample of 121 pediatric patients with JIA, but did find an association with the rs1801133 SNP in MTHFR that we did not investigate in this study. 23 …”
Section: Discussionmentioning
confidence: 99%